ANALISIS PENGARUH MODAL INTELEKTUAL TERHADAP PROFITABILITAS, PRODUKTIFITAS, DAN PENILAIAN PASAR PERUSAHAAN (Studi Kasus Pada 35 Perusahaan LQ-45 di Bursa Efek Indonesia Periode 2012-2014) - Agusta, Alwin; Adiwibowo, Agustinus Santosa (Diponegoro Journal of Accounting, 2017)
Purpose – Intelectual capital (IC) shows a significant frowing acceptable as a worthytopic of academic investigation and practical implication. The purspose of this study is to measure the influence of intellectual capital on firms; profitability, productivity, and market valuation.Methodology design – The empirical data were drawn from a panel consisting of 35 Indonesian companies listed in the Indonesian Stock Exchange (IDX), from several different economic sectors, observed over the three-year period of 2012 to 2014. Regeression models were examined in order to test the hyposteses included in the proposed conceptual framework.Findings – Result success to support most of the hypotheses,concluding that there are two significant influence of intellectual capital on productivity and market valuation. But failed to support the first hypotheses that is the influence of intellectual capital on profitability. Despite the fact thai intellectual capital is increasingly recognized as an important strategic asset for sustainable corporate competitive disadvantage, the result of the present study give rise to various arguments, criticism and further research on the subject.Research Limitation – The little amount of data for the appropriate analysis and the relatively narrow three-year period for data collection, research subject only 35companies that is listed on Indonesian Stock Exchange are the main limitation of the present study.